2014
DOI: 10.1016/j.jsat.2013.08.017
|View full text |Cite
|
Sign up to set email alerts
|

Meeting health and psychological needs of women in drug treatment court

Abstract: We explored healthcare-related experiences of women drug court participants through combining context from the Socio-Ecological Model with motivation needs for health behavior as indicated by self-determination theory. Five focus groups with 8 women drug court participants, 8 court staff, and 9 community service providers were examined using qualitative framework analysis. Themes emerged across the Socio-Ecological Model and were cross-mapped with self-determination theory-defined motivation needs for autonomy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

4
6

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 51 publications
1
41
1
Order By: Relevance
“…While this review found that women who received more and better-matched services had better reunification rates, intrinsic motivational factors also play an integral role (Blakey, 2012). Programs to facilitate care for mothers with a SUD need to take this into consideration and include programs that deliver comprehensive care with a holistic approach that address multiple layers including motivational needs for health behavior change (Morse et al, 2014). Additionally, treatment satisfaction and retention may increase if social determinants of health such as social networks and support, education, employment and economic issues are addressed whilst in treatment (Greenfield et al, 2007).…”
Section: Discussionmentioning
confidence: 94%
“…While this review found that women who received more and better-matched services had better reunification rates, intrinsic motivational factors also play an integral role (Blakey, 2012). Programs to facilitate care for mothers with a SUD need to take this into consideration and include programs that deliver comprehensive care with a holistic approach that address multiple layers including motivational needs for health behavior change (Morse et al, 2014). Additionally, treatment satisfaction and retention may increase if social determinants of health such as social networks and support, education, employment and economic issues are addressed whilst in treatment (Greenfield et al, 2007).…”
Section: Discussionmentioning
confidence: 94%
“…Court ordered treatment can move an individual from coercive control to intrinsic motivation (Kothari, Butkiewicz, Williams, Jacobson, Morse, & Cerulli, 2014; Morse, Cerulli, Bedell et al ., 2014). It is possible that probation can become that legal leverage youth need to connect to care and begin seeing their behavior through a different lens (Lamberti et al ., 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Of the studies that exist, two (Mackinem and Higgins 2007;Wolf and Colyer 2001) utilized field observations to study court hearing interactions and five others (Farole and Cissner 2005;Francis and Abel 2014;Goldkamp, White, and Robinson 2001b;Morse et al 2014;Narag, Maxwell, and Lee 2013) used focus groups and interviews to explore clients and court personnel's perceptions and opinions about existing drug programs. While these few exceptions exist, it is surprising that drug/DUI court clients' stories and experiences are largely left out and remain unexamined.…”
Section: Past Studies On Drug/dui Courtsmentioning
confidence: 99%